Arabidopsis Triphosphate Tunnel Metalloenzyme2 Is a Negative Regulator of the Salicylic Acid-Mediated Feedback Amplification Loop for Defense Responses. Issue 2 (2nd September 2014) - Ung, Huoi; Moeder, Wolfgang; Yoshioka, Keiko
Abstract : A triphosphate tunnel metalloenzyme is a negative regulator in amplification of SA -dependent defense responses . Abstract: The triphosphate tunnel metalloenzyme (TTM) superfamily represents a group of enzymes that is characterized by their ability to hydrolyze a range of tripolyphosphate substrates. Arabidopsis ( Arabidopsis thaliana ) encodes three TTM genes, AtTTM1, AtTTM2, and AtTTM3 . Although AtTTM3 has previously been reported to have tripolyphosphatase activity, recombinantly expressed AtTTM2 unexpectedly exhibited pyrophosphatase activity. AtTTM2 knockout mutant plants exhibit an enhanced hypersensitive response, elevated pathogen resistance against both virulent and avirulent pathogens, and elevated accumulation of salicylic acid (SA ) upon infection. In addition, stronger systemic acquired resistance compared with wild-type plants was observed. These enhanced defense responses are dependent on SA, PHYTOALEXIN-DEFICIENT4, and NONEXPRESSOR OF PATHOGENESIS-RELATED GENES1 . Despite their enhanced pathogen resistance, ttm2 plants did not display constitutively active defense responses, suggesting that AtTTM2 is not a conventional negative regulator but a negative regulator of the amplification of defense responses. The transcriptional suppression of AtTTM2 by pathogen infection or treatment with SA or the systemic acquired resistance activator benzothiadiazole further supports this notion. Such transcriptional regulation is conserved among TTM2 orthologs in the crop plants soybean ( Glycine max ) and canola ( Brassica napus ), suggesting that TTM2 is involved in immunity in a wide variety of plant species. This indicates the possible usage of TTM2 knockout mutants for agricultural applications to generate pathogen-resistant crop plants.